Philippine regional cuisine - Melchor, Jose Antonio Miguel; Vizconde, Angelie Marie (Sta. Cruz, Manila : Edric Publishing House, 2021)
The Philippines is a country with beautiful nature and delicious foods. It is a land of diversity, in which history and present mix, offering a great variety of cultures, languages and foods.
Chapter 1. Philippine Cuisine -- 2. History of the Philippines & Its Food: A Timeline -- 3. Native Ingredients -- 4. Luzon Cuisine -- 5. Mindanao Cuisine -- 6. Mindanao Cuisine -- 7. Cooking Methods -- 8. Philippine Condiments -- References.
Includes bibliographical references.
Keywords: COOKING, PHILIPPINE